2013
DOI: 10.1128/aem.01791-13
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Nodule-Specific Cysteine-Rich Peptides Induce Membrane Depolarization-Associated Changes in the Transcriptome of Sinorhizobium meliloti

Abstract: bLeguminous plants establish symbiosis with nitrogen-fixing alpha-and betaproteobacteria, collectively called rhizobia, which provide combined nitrogen to support plant growth. Members of the inverted repeat-lacking clade of legumes impose terminal differentiation on their endosymbiotic bacterium partners with the help of the nodule-specific cysteine-rich (NCR) peptide family composed of close to 600 members. Among the few tested NCR peptides, cationic ones had antirhizobial activity measured by reduction or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
131
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(142 citation statements)
references
References 25 publications
(26 reference statements)
9
131
0
2
Order By: Relevance
“…These proteins regulate the transport of ions, minerals, siderophores, and polysaccharides, suggesting that the increased regulation of levels of these ions and molecules is important during cellular adaptation to NCR247 peptide-mediated stress. Interestingly, we also observed that treatment of S. meliloti with a sublethal dose of NCR247 activated the expression of rpoH1 and several RpoH1-regulated genes, similar to the effects seen when S. meliloti cells were treated with a lethal dose of NCR247 (11). These data suggest that, even at sublethal levels, NCR247-peptide treatment activates a cytoplasmic stress response in S. meliloti cells.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…These proteins regulate the transport of ions, minerals, siderophores, and polysaccharides, suggesting that the increased regulation of levels of these ions and molecules is important during cellular adaptation to NCR247 peptide-mediated stress. Interestingly, we also observed that treatment of S. meliloti with a sublethal dose of NCR247 activated the expression of rpoH1 and several RpoH1-regulated genes, similar to the effects seen when S. meliloti cells were treated with a lethal dose of NCR247 (11). These data suggest that, even at sublethal levels, NCR247-peptide treatment activates a cytoplasmic stress response in S. meliloti cells.…”
Section: Discussionsupporting
confidence: 62%
“…In addition to provoking bacteroid differentiation, NCR peptides exhibit antimicrobial activity (4,9,11). NCR peptides are similar to plant defensins, which are antimicrobial peptides (AMPs) that function in the innate immune response (4,12,13).…”
mentioning
confidence: 99%
See 3 more Smart Citations